Blockchain Interoperability Frameworks: A Comparative Analysis of Cross-Chain Solutions for DLT Innovation - Varun Tamminedi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article comprehensively analyzes blockchain interoperability as a crucial frontier in distributed ledger technology (DLT) innovation. Through systematic examination of current interoperability solutions, technical challenges, and implementation frameworks, the study provides insights into the evolving landscape of cross-chain communication and its implications for industry adoption. The article evaluates prominent interoperability frameworks, including the Interledger Protocol, Cosmos Network, Polkadot, and Canton Network, analyzing their architectural approaches, security mechanisms, and practical applications. Key findings reveal significant progress in addressing fundamental challenges such as protocol standardization, consensus mechanism compatibility, and scalability constraints while highlighting remaining cross-chain security and governance obstacles. The article demonstrates substantial benefits of blockchain interoperability across various sectors, with notable implementations in supply chain management reducing documentation errors by 65%, cross-border financial services decreasing settlement times from days to minutes, and healthcare data exchange improving information accessibility by 75%. Through examination of technical requirements, governance models, and risk mitigation strategies, this research establishes a comprehensive framework for implementing interoperable blockchain solutions while maintaining security and regulatory compliance. The article contributes to the growing knowledge in DLT innovation and provides practical insights for stakeholders working towards achieving seamless blockchain interoperability.
Keywords: Blockchain Interoperability; Cross-Chain Communication Protocols; Distributed Ledger Technology (DLT); Multi-Chain Integration Architecture; Consensus Mechanism Compatibility